The Influence of Infrastructure Facilities and Teacher Pedagogic Competence on Student Satisfaction in Public High Schools in Pekanbaru City - Nikmalini Nikmalini; Sumarno Sumarno; Erni Erni (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study aims to examine the impact of infrastructure and teacher pedagogic ability on student happiness at Pekanbaru State Senior High School. This research is quantitative research with the type of ex post facto research. The population in this study were students at Pekanbaru City Public High School. The sampling technique used in this study was a purposive sampling technique. In this case, a sample of 231 students was taken. Questionnaires was used as the data collection technique distributed using Google Forms. The data analysis technique used was descriptive statistical analysis and inferential statistical analysis using the SPSS (Statistics Package for Social Science) Version.2 2 programs. From the results, it can be seen that the calculated F value is 10.684 while the F table is 3.03. F table F count, namely 3.03 10.684, so H0 is rejected. Then, based on the sig value of 0.001 0.05, it can be concluded that there is a significant influence between infrastructure and teacher pedagogical competence on student satisfaction in Pekanbaru City Public High School. Then, It can be seen from the Coefficients Beta values of 0.100 for infrastructure and 0.542 for teacher pedagogic competence. This means that for every increase in infrastructure in one unit, student satisfaction will increase by 0.100 one team. Then, for every one-unit increase in teacher pedagogic competence, student satisfaction will increase by 0.542 one unit. So, the research results show that infrastructure and teacher pedagogic competence affect student satisfaction at Pekanbaru City Public High School.